Self-Compassion and Smartphone Addiction Tendency Among College Students: The Chain-Mediating Effect of Self-Concept Clarity and Experiential Avoidance - Yin Qiu; Shaoying Gong; Yang Yang; Jing Wang; Liping Tan (Behavioral Sciences)
Smartphone addiction has emerged as a pressing public health issue in recent years, which negatively impacts university students’ academic performance, physical and mental health, and social functioning. Therefore, it is crucial to explore the significant factors related to smartphone addiction. While previous research has suggested a potential link between self-compassion and problematic internet or smartphone use, studies specifically examining the relationship between self-compassion and smartphone addiction tendency remain limited. From a positive psychology perspective, this study aims to explore the relationship between self-compassion and smartphone addiction tendency, as well as its internal mechanism. A total of 641 Chinese college students were recruited to complete online questionnaires assessing their self-compassion, self-concept clarity, experiential avoidance, and smartphone addiction tendency. The results show that self-compassion not only directly and negatively predicts smartphone addiction tendency, but also indirectly predicts it through the independent mediating effects of self-concept clarity and experiential avoidance. Additionally, there is a chain-mediating effect of self-concept clarity and experiential avoidance. This study provides a new perspective for the prevention and intervention of smartphone addiction tendency among college students.